Evaluasi Profil Penyimpanan Obat di Rumah Sakit X Kabupaten Semarang Terhadap Pelayanan Kefarmasian - Rissa Maharani Dewi; Zuspita Yanti; Nala Evania; Salvira Anindya; Launiz Zamarda Julianty (Sultan Agung Islamic University, 2026)
Background: Drug storage practices in the pharmaceutical warehouse of Hospital X are generally well implemented,indicators meeting operational requirements. However, specific improvements are still required, particularly in the management of high-risk drug categories and temperature monitoring practices, to strengthen patient safety and maintain optimal pharmaceutical quality. Methods: This study used a descriptive observational design. Data were collected prospectively through direct observation using a structured checklist consisting of four assessment domains: storage requirements, storage components, storage methods, and storage facilities. Each item was scored as compliant (1) or non-compliant (0), and the final score was converted into a compliance percentage. Results: Storage requirement indicators demonstrated full compliance (100%). Storage component indicators showed a compliance level 75%, nonconformities identified in the security and labeling of concentrated electrolytes. Storage methods achieved 100% compliance, reflecting consistent implementation of FIFO FEFO,alphabetical ordering, therapeutic grouping, and LASA separation. Facilities and infrastructure obtained an 81% compliance score, with gaps identified in temperature recording practices and flooring specifications. Overall compliance for drug storage was 80%. Conclusion: Drug storage practices in the pharmaceutical warehouse of Hospital X are categorized as good; however, improvements are required in high-alert medication management and temperature monitoring to enhance safety and ensure continuous pharmaceutical quality.